Maternal Vitamin D and Inulin Supplementation in Oxidized Oil Diet Improves Growth Performance and Hepatic Innate Immunity in Offspring Mice - Guangrong Xie; Qipeng Zhang; Zhengfeng Fang; Lianqiang Che; Yan Lin; Shengyu Xu; Yong Zhuo; Lun Hua; Xuemei Jiang; Jian Li; Mengmeng Sun; Yuanfeng Zou; et al. (MDPI AG, 2023)
Dietary oxidized fat contains harmful materials such as hydrogen peroxide and malondialdehyde (MDA). Excessive oxidized fat intake during pregnancy and lactation not only leads to maternal body injury but also damages offspring health. Our previous study demonstrated that vitamin D (VD) had antioxidative capability in sows. This study was conducted to investigate the effect of maternal VD and inulin supplementation in oxidized oil diet on the growth performance and oxidative stress of their offspring. Sixty 5-month-old C57BL/6N female mice were randomly divided into five groups: Control group (basal diet, n = 12), OF group (oxidized-soybean-oil-replaced diet, n = 12), OFV group (oxidized-soybean-oil-replaced diet + 7000 IU/kg VD, n = 12), OFI group (oxidized-soybean-oil-replaced diet + 5% inulin, n = 12) and OFVI group (oxidized-soybean-oil-replaced diet + 7000 IU/kg VD + 5% inulin, n = 12). Mice were fed with the respective diet during pregnancy and lactation. The offspring were then slaughtered on day 21 of age at weaning. Results showed that a maternal oxidized oil diet impaired body weight and liver weight gain of offspring during lactation compared to the control group, while maternal VD, inulin or VD and inulin mixture supplementation reversed this effect. In addition, the activity of T-AOC in the liver of offspring was lower in the OF group than that in the control group, but could be restored by maternal VD and inulin mixture supplementation. Furthermore, the gene expression of both proinflammatory and anti-inflammatory cytokines, such as Il-6, Tnfα and Il-10, in offspring liver were downregulated by a maternal oxidized oil diet compared with the control group, but they were restored by maternal VD or VD and inulin mixture supplementation. The expressions of Vdr and Cyp27a1 were decreased by a maternal oxidized oil diet compared with the control group, while they could be increased by VD or VD and inulin mixture supplementation. Conclusion: maternal oxidized oil diet intake could impair the growth performance by inducing oxidative stress, but this can be relieved by maternal VD and inulin supplementation.